2004
DOI: 10.1021/je0496903
|View full text |Cite
|
Sign up to set email alerts
|

Densities and Viscosities of Binary Mixtures of Paraldehyde + Propylene Carbonate at (288.15, 293.15, 298.15, 303.15, and 308.15) K

Abstract: The densities and viscosities of binary mixtures of paraldehyde + propylene carbonate have been measured at (288.15, 293.15, 298.15, 303.15, and 308.15) K. From these measurements, excess molar volumes (V E) and viscosity deviations (δη) were calculated. These results were fit to a Redlich−Kister polynomial. The results were discussed in terms of molecular interactions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
20
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 12 publications
0
20
0
Order By: Relevance
“…The experimental technique for density and viscosity measurements was the same as that used previously. 7 For all of the measurements, temperature was controlled by circulating the water through an ultra thermostat Julabo F-25 (made in Germany), which has a temperature precision of (0.02°C. Table 2 lists the experimental values of densities F and viscosities η of the binary mixtures of 2,4,6-trimethyl-1,3,5-trioxane + n-alcohols at 298.15, 303.15, and 308.15 K.…”
Section: Methodsmentioning
confidence: 99%
“…The experimental technique for density and viscosity measurements was the same as that used previously. 7 For all of the measurements, temperature was controlled by circulating the water through an ultra thermostat Julabo F-25 (made in Germany), which has a temperature precision of (0.02°C. Table 2 lists the experimental values of densities F and viscosities η of the binary mixtures of 2,4,6-trimethyl-1,3,5-trioxane + n-alcohols at 298.15, 303.15, and 308.15 K.…”
Section: Methodsmentioning
confidence: 99%
“…The experimental repeatability of the viscosity measurements of each solution was found to be ±0.2 %, with an uncertainty of 3 × 10 −2 . The details of the density and viscosity measurements are given in previous papers [12][13][14].…”
Section: Methodsmentioning
confidence: 99%
“…The present paper is a continuation of our study on the thermodynamic properties of liquid mixtures containing propylene carbonate as one of the components [9][10][11][12][13][14]. We report here densities and viscosities of binary mixtures of propylene carbonate with THF, 1,4-dioxane, and acetylacetone at (288.…”
mentioning
confidence: 98%
“…The study of the ultrasonic velocity in liquids and liquid mixtures and its influence on molecular structure were studied by several researchers. [11][12][13][14][15][16][17][18][19][20][21][22] Ultrasonic studies in binary mixtures of hydrocarbon liquids with several alcohols were carried [23][24] and observed, "Ultrasonic velocity has a parabolic variation with the composition of the mixture in several aqueous mixtures of alcohols". In many studies carried out 25 , it was observed that " the negative excess molar volume can be complimented to the strong interaction between unlike molecules through hydrogen bonding for the binary mixtures of 1,1,2,2-tetrabromoethane with 1-pentanol, 1-hexanol, 1-heptanol, 1-octanol and 1-decanol at the temperatures of 298.15 and 303.15 K and concluded that such a behavior is the result of several opposing effects.…”
Section: Introductionmentioning
confidence: 99%